Simplified local anesthesia technique for external dacryocystorhinostomy without nasal packing: a new technique and pilot study outcome - Tawfik HA (Dove Medical Press, 2013)
Hatem A Tawfik,1 Osama R Youssef21Department of Ophthalmology, 2Department of Anesthesiology, Ain Shams University, Cairo, EgyptBackground: The purpose of this paper is to describe a simplified local anesthesia technique for external dacryocystorhinostomy (EXT-DCR).Methods: In this pilot, retrospective, noncomparative, interventional case series, 448 patients (480 eyes) underwent EXT-DCR using a simplified local anesthesia technique. Nasal mucosal anesthesia was achieved using combined application of 6 mL of oxymetazoline 0.025% nasal spray and lidocaine 1% in the same spray bottle, without any packing of the nose with either pledgets or ribbon gauze. Local infiltration anesthesia consisted of subcutaneous injection of a 7 mL mixture of 2% lidocaine with 1:100,000 epinephrine injected on the flat side of the nose beneath the incision site, in addition to a second medial peribulbar injection (3 mL, 2% lidocaine without epinephrine).Results: Successful unilateral or bilateral EXT-DCR was achieved in 432/448 patients (96.4%). Four patients could not tolerate the procedure under local anesthesia and were converted to general anesthesia. Four patients required additional local anesthetic injections because of intolerable pain. Heavy sedation was essential in eight uncooperative patients because surgical manipulation was impossible. The remaining patients tolerated the procedure well. The intraoperative bleeding rate was very low except in one patient. Mean operative time was 16 minutes. Severe postoperative epistaxis was observed in four patients. Temporary anosmia developed in one patient.Conclusion: Our simplified local anesthesia approach of EXT-DCR is convenient for the patient because it avoids unnecessary nasal packing. It is also safe and effective, as evidenced by the high rate of successful completion of the procedure without conversion to general anesthesia or the need for supplemental local anesthesia.Keywords: local anesthesia, external dacryocystorhinostomy